(untitled) (Asia Pacific Journal of Social Innovation, 2024)
Sphygmomanometers and stethoscopes are important vital signs taking paraphernalia for monitoring patient’s condition in the hospital wherein thorough disinfecting of these paraphernalia are sometimes neglected. Swab samples were taken from sphygmomanometer inner cuffs and stethoscope bells and diaphragms from the different special areas in Gregorio T. Lluch Memorial Hospital (GILMH), Iligan City, namely the Outpatient Department (OPD), Emergency Room (DR), Delivery Room (DR) and Recovery Room (RR). Morphological, colonial and biochemical tests were done to identify the bacteria present in the samples.. Out of the 29 selected bacterial isolates, 13.8% were presumptively identified to be Staphylococcus sp., Bacillus sp., and Lactobacillus sp., respectively. Streptococcus sp., Microccous sp, Neisseria sp., and Pseudomonas sp. comprised 10.3% of the total isolates and only 3.4% was classified as coagulase-negative staphylococcus whereas the remaining 3.4 % was unidentified. Accordingly, the most common causes of nosocomial infections are Escherichia coli, Staphylococcus aureus, and Pseudomonas sp., all of which are found significantly in the samples taken from GTLMH. In the sphygmomanometer cuffs, a high number of Microbacillus sp. was found in the OPD, while Lactobacillus sp. was found to be higher in number in the ER and DR. In the stethoscopes, bacteria were found to be evenly distributed in the four areas. Of these areas, the OPD was found to have the most number of identified bacteria which may be attributed to the number of patients going there for consultation. ER and RR have the least number of bacteria identified possibly because they accommodate lesser number of patients. With this study, health care workers would be aware of the on going problem and be able to act on them.